HIV prevalence among high school learners - opportunities for schools-based HIV testing programmes and sexual reproductive health services - Kharsany Ayesha BM; Mlotshwa Mukelisiwe; Frohlich Janet A; Yende Zuma Nonhlanhla; Samsunder Natasha; Abdool Karim Salim S; Abdool Karim Quarraisha (BMC, 2012)
Abstract Background Young girls in sub Saharan Africa are reported to have higher rates of human immunodeficiency virus (HIV) infection compared to boys in the same age group. Knowledge of HIV status amongst high schools learners provides an important gateway to prevention and treatment services. This study aimed at determining the HIV prevalence and explored the feasibility of HIV testing among high school learners. Methods Between September 2010 and February 2011, a linked, anonymous cross-sectional survey was conducted in two public sector high schools in the rural KwaZulu-Natal midlands. Following written informed consent, dried blood spot samples (DBS) were collected and tested for HIV. The overall and age-specific HIV prevalence were compared with select demographic variables. Results The HIV prevalence in learners aged 12 to 25 in school A was 4.7% (95% CI 2.8-6.5) compared to 2.5% (95% CI 1.6-3.5) in school B, (p = 0.04). Whilst the HIV prevalence was similar for boys at 1.3% (95% CI 0-2.8) in school A and 1.7% (95% CI 0.5-2.8) in school B, the prevalence in girls was consistently higher and was 7.7% (95% CI 4.5-10.9) in school A and 3.2% (95% CI 1.8-4.6) in school B. The age-specific HIV prevalence in girls increased 1.5 to 2 fold for each two year age category, while for boys the prevalence was stable across all age groups. Conclusions The high HIV prevalence in female learners underscores the importance of sexual reproductive health and schools-based HIV testing programs as an important gateway to prevention and treatment services.